Altered Gut Microbiota in H1-Antihistamine-Resistant Chronic Spontaneous Urticaria Associates With Systemic Inflammation - Song, Yao; Dan, Kena; Yao, Zhengqiu; Yang, Xi; Chen, Bangtao; Hao, Fei (Frontiers in Cellular and Infection Microbiology, 2022)
Background and Objective: Chronic spontaneous urticaria (CSU) is a histamine-mediated inflammatory skin disease, and second-generation non-sedating H1-antihistamines (nsAH) at licensed doses have long been the first-line therapy in CSU. However, about 50% of patients are resistant to nsAH, and the precise pathogenesis remains largely unknown but seems to be associated with low-level systemic or intestinal inflammation. We aim to determine the fecal microbial composition and clarify its correlation with CSU's clinical profiles with nsAH resistance. Methods: 25 CSU patients with or 19 CSU patients without nsAH resistance and 19 healthy controls (HC) were enrolled in this study. The intestinal microbiome was detected by 16S rRNA sequencing. The data were analyzed using R language software. Results: Significantly higher urticarial activity score for 7 days, stool calprotectin, erythrocyte sedimentation rate, serum C-reactive protein, and interleukin-6, but much lower alpha-diversity and evenness of fecal bacterial community were observed in CSU patients with nsAH resistance than in those without (P＜0.05 for all variables). Compared to patients with nsAH-responsiveness, the abundance of fecal genera Prevotella, Megamonas, and Escherichia were significantly increased, while that Blautia, Alistipes, Anaerostipes, and Lachnospira were remarkably reduced in nsAH-resistant patients (uncorrected P＜0.05 for all variables). Finally, systemic not intestinal inflammation degree was positively correlated with genera Escherichia, while negatively with genera Blautia, Dorea, Lactobacillus, Eubacterium_hallii_group, and Roseburia. CSU without nsAH resistance and HC individuals showed almost unchanged genera bacterium. Conclusions: Among CSU patients, pro-inflammation phenotype relating to enteric dysbacteriosis features nsAH resistance in CSU patients. The results provide clues for future microbial-based or anti-inflammatory therapies on nsAH resistant CSU.